23.5k views
0 votes
Please help: 3(x+2)+2(x-4)=x-3(x+3)

User KVK
by
5.7k points

2 Answers

2 votes

Assignment:
\bold{Solve \ Equation: \ 3\left(x+2\right)+2\left(x-4\right)=x-3\left(x+3\right)}

<><><><><><><>

Answer:
\boxed{\bold{x=-1}}

<><><><><><><>

Explanation:
\downarrow\downarrow\downarrow

<><><><><><><>

[ Step One ] Expand
\bold{-3\left(x+3\right)}


\bold{-3x-9}

[ Step Two ] Rewrite Equation


\bold{5x-2=x-3x-9}

[ Step Three ] Add Similar Elements
\bold{x-3x=-2x}


\bold{5x-2=-2x-9}

[ Step Four ] Expand
\bold{3\left(x+2\right)+2\left(x-4\right)}


\bold{5x-2}

[ Step Five ] Rewrite Equation


\bold{5x-2=-2x-9}

[ Step Six ] Add 2 To Both Sides


\bold{5x-2+2=-2x-9+2}

[ Step Seven ] Simplify


\bold{5x=-2x-7}

[ Step Eight ] Add 2x To Both Sides


\bold{5x+2x=-2x-7+2x}

[ Step Nine ] Simplify


\bold{7x=-7}

[ Step Ten ] Divide Both Sides By 7


\bold{(7x)/(7)=(-7)/(7)}

[ Step Eleven ] Simplify


\bold{x=-1}

<><><><><><><>


\bold{\rightarrow Mordancy \leftarrow}

User Comecme
by
4.6k points
1 vote

*Distribute*

3x+6+2x-8=x-3x-9

*Combine like terms*

5x-2=-2x-9

*Add 2x to both sides*

7x-2=-9

*Add 2 to both sides*

7x=-7

*Divide both sides by 7*

x=-1

Hope this helps!!

User Martin Liversage
by
5.6k points